Analisis Kinerja Keuangan Dengan Menggunakan Metode EVA dan MVA Pada PT Bank Syariah Indonesia Tbk - Gurhanawan Gurhanawan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Good financial performance will help management achieve company goals. The aim of this research is to examine the financial performance of Bank Syariah Indonesia after the merger, namely the period 2021 - 2023. This research is quantitative descriptive research, using EVA and MVA analysis. The results of this research show that the financial performance value using EVA and MVA is always positive, this means that the financial performance of PT. Bank Syariah Indonesia is good in terms of economic growth and market development.